Associations of dry skin, skin care habits, well‐being, sleep quality and itch in nursing home residents: Results of a multicentre, observational, cross‐sectional study - Elisabeth Hahnel; Ulrike Blume‐Peytavi; Jan Kottner (Wiley, 2019)
Abstract Aim Dry skin is one of the most frequent cutaneous problems in aged long‐term care residents. Although it is clinically relevant, the impact on quality of life is unclear. The objective was to measure well‐being, sleep quality and itch in nursing home residents being 65 years and older and to explore possible associations with demographics, dry skin and skincare habits. Design Multicentre, observational, cross‐sectional. Methods Sleep quality was assessed with the Richards‐Campbell Sleep Quality Questionnaire, well‐being with the WHO‐Five Well‐being Index and itch with the 5‐D Itch scale. Skin dryness was measured using the Overall Dry Skin score. Results A total of 51 residents were included. The item scores of the sleep quality and itch questionnaires were strongly associated with each other. Demographics, dry skin and skincare habits were not associated with the questionnaires. It is unclear whether basic skincare activities can improve the quality of life in this population.